2020
DOI: 10.1038/s41392-020-00301-9
|View full text |Cite
|
Sign up to set email alerts
|

Disease severity dictates SARS-CoV-2-specific neutralizing antibody responses in COVID-19

Abstract: COVID-19 patients exhibit differential disease severity after SARS-CoV-2 infection. It is currently unknown as to the correlation between the magnitude of neutralizing antibody (NAb) responses and the disease severity in COVID-19 patients. In a cohort of 59 recovered patients with disease severity including severe, moderate, mild, and asymptomatic, we observed the positive correlation between serum neutralizing capacity and disease severity, in particular, the highest NAb capacity in sera from the patients wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
185
5
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(226 citation statements)
references
References 31 publications
(59 reference statements)
32
185
5
4
Order By: Relevance
“…2B and table S1). Antibody titers were observed to correlate with disease severity, with lower antibody titers observed in patients with mild COVID-19 disease and higher titers in severe cases, consistent with findings from other published studies ( 23,24 ). ACE2-competitive antibody titers were detectable in only 33% (n = 3/9) of patients with mild disease, while these antibodies were present in 82% (n = 14/17) of patients with moderate disease and in 100% (n = 7/7) in patients with severe disease.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…2B and table S1). Antibody titers were observed to correlate with disease severity, with lower antibody titers observed in patients with mild COVID-19 disease and higher titers in severe cases, consistent with findings from other published studies ( 23,24 ). ACE2-competitive antibody titers were detectable in only 33% (n = 3/9) of patients with mild disease, while these antibodies were present in 82% (n = 14/17) of patients with moderate disease and in 100% (n = 7/7) in patients with severe disease.…”
Section: Resultssupporting
confidence: 90%
“…Understanding which components of the immune system are needed to confer optimal immune protection against SARS-CoV-2 infection and COVID-19 disease is critical to the development of effective vaccines. It has been reported that individuals with mild COVID-19 disease observe low or undetectable levels of neutralizing antibodies ( 23,24 ), and approximately 35% of SARS-CoV-2 naïve individuals have cross-reactive CD4 + T-cell responses to SARS-CoV-2 antigens due to prior infection by other common-cold coronaviruses ( 33 ). In this study, a clear association between higher antibody titers specific to SARS-CoV-2 and more severe disease was observed, using a panel of 41 human convalescent sera samples collected from recovered COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…1D). Generally, antibodies confer favorable humoral immunity; however, massive immune complexes can be a driving force of tissue permeability as seen in systemic lupus erythematosus, in agreement with Chen et al’s observation that higher virus-specific antibody titers correlate with disease severity (17). In summary, decreased TH17 type T cells and increased IgA secreting B cells may augment the disease severity.…”
Section: Mainsupporting
confidence: 78%
“…Asymptomatic or mild symptomatic patients may possibly mount robust SARS-CoV-2 specific CD8 + T cell responses, which can provide protection by directly eliminating the target cells infected by the virus. However, due to the lack of immunity provided by nAb, these individuals might suffer from SARS-CoV-2 reinfection (200,201).…”
Section: Humoral Responsementioning
confidence: 99%
“…Although vaccination provides T cells-based virus-specific immunity, the path to its development is long, so the use of adoptive cell transfer techniques from healthy individuals who recovered from COVID-19 and developed an effective cell response is probably the fastest way to treat critically ill individuals (297). Besides that, as mentioned before, asymptomatic or mild symptomatic patients may possibly mount robust SARS-CoV-2 specific CD8+ T cell responses (200,201), therefore, the use of these individuals' cells to treat critically ill patients with COVID-19 can be a promising tool.…”
Section: Immune Cell-based Therapymentioning
confidence: 99%